Enticing Dimples: A Novel Observational Study Comparing the Preexisting Landmarks for Facial Dimple Creation Using 3D-Scanned Facial Images - Lena Elizabath David; Madhubari Vathulya; Smruti Srinivasan; Yogesh Bahurupi; N Nasida Fathima (Indian Journal of Plastic Surgery)
Background Dimpleplasty, a cosmetic procedure for creating dimples, is gaining popularity. However, the ideal site for dimple creation remains subjective. This study aimed to determine the optimal dimple placement using a three-dimensional (3D) model, reviewing panelists' preferences based on facial proportions and average ratings.